Estimation of apparent binding constant of complexes of selected acyclic nucleoside phosphonates with β-cyclodextrin by affinity capillary electrophoresis - Šolínová, Veronika; Mikysková, Hana; Kaiser, Martin Maxmilián; Janeba, Zlatko; Holý, Antonín; Kašička, Václav (Electrophoresis, 2016)
Affinity capillary electrophoresis (ACE) has been applied to estimation of apparent binding constant of complexes of (R,S)-enantiomers of selected acyclic nucleoside phosphonates (ANPs) with chiral selector β-cyclodextrin (βCD) in aqueous alkaline medium. The noncovalent interactions of five pairs of (R,S)-enantiomers of ANPs-based antiviral drugs and their derivatives with βCD were investigated in the background electrolyte (BGE) composed of 35 or 50 mM sodium tetraborate, pH 10.0, and containing variable concentration (0-25 mM) of βCD. The apparent binding constants of the complexes of (R,S)-enantiomers of ANPs with βCD were estimated from the dependence of effective electrophoretic mobilities of (R,S)-enantiomers of ANPs (measured simultaneously by ACE at constant reference temperature 25°C inside the capillary) on the concentration of βCD in the BGE using different nonlinear and linear calculation methodologies. Nonlinear regression analysis provided more precise and accurate values of the binding constants and a higher correlation coefficient as compared to the regression analysis of the three linearized plots of the effective mobility dependence on βCD concentration in the BGE. The complexes of (R,S)-enantiomers of ANPs with βCD have been found to be relatively weak - their apparent binding constants determined by the nonlinear regression analysis were in the range 13.3-46.4 L/mol whereas the values from the linearized plots spanned the interval 12.3-55.2 L/mol.
Keywords: Organophosphonates; Acyclic nucleoside phosphonates; Affinity capillary electrophoresis; Nucleotide analogs; Binding Sites; beta-Cyclodextrins; Stereoisomerism; elektroforéza kapilární; vazebná místa; nukleosidy; Electrophoresis, Capillary; beta-cyklodextriny; Nucleosides; Binding constant; stereoizomerie; organofosfonáty; β-Cyclodextrin